The Integrated HIV-1 Provirus in Patient Sperm Chromosome and Its Transfer into the Early Embryo by Fertilization - Wang, Dian; Li, Lian-Bing; Hou, Zhi-Wei; Kang, Xiang-Jin; Xie, Qing-Dong; Yu, Xiao-jun; Ma, Ming-Fu; Ma, Bo-Lu; Wang, Zheng-Song; Lei, Yong; Huang, Tian-Hua (PloS one, 2011)
Complete understanding of the route of HIV-1 transmission is an important prerequisite for curbing the HIV/AIDS pandemic. So far, the known routes of HIV-1 transmission include sexual contact, needle sharing, puncture, transfusion and mother-to-child transmission. Whether HIV can be vertically transmitted from human sperm to embryo by fertilization is largely undetermined. Direct research on embryo derived from infected human sperm and healthy human ova have been difficult because of ethical issues and problems in the collection of ova. However, the use of inter-specific in vitro fertilization (IVF) between human sperm and hamster ova can avoid both of these problems. Combined with molecular, cytogenetical and immunological techniques such as the preparation of human sperm chromosomes, fluorescent in situ hybridization (FISH), and immunofluorescence assay (IFA), this study mainly explored whether any integrated HIV provirus were present in the chromosomes of infected patients' sperm, and whether that provirus could be transferred into early embryos by fertilization and maintain its function of replication and expression. Evidence showed that HIV-1 nucleic acid was present in the spermatozoa of HIV/AIDS patients, that HIV-1 provirus is present on the patient sperm chromosome, that the integrated provirus could be transferred into early embryo chromosomally integrated by fertilization, and that it could replicate alongside the embryonic genome and subsequently express its protein in the embryo. These findings indicate the possibility of vertical transmission of HIV-1 from the sperm genome to the embryonic genome by fertilization. This study also offers a platform for the research into this new mode of transmission for other viruses, especially sexually transmitted viruses.